2017
DOI: 10.1186/s13104-017-2626-5
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility pattern of clinical isolates of Burkholderia pseudomallei in Bangladesh

Abstract: BackgroundMelioidosis an infectious disease, caused by a Gram negative bacterium called Burkholderia pseudomallei, is endemic in Bangladesh. This organism is sensitive to limited number of antimicrobial agents and need prolonged treatment. There is no comprehensive data on the antimicrobial susceptibility profile of B. pseudomallei isolated in Bangladesh over last several years. The present study aimed to determine the antimicrobial susceptibility pattern of B. pseudomallei isolated in a tertiary care hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 22 publications
6
26
0
Order By: Relevance
“…As reported by Inglis et al, the API 20NE method identified only 37% of the B. pseudomallei isolates.2 B. pseudomallei has a high degree of phenotypic plasticity and the colony morphology varies greatly within and between samples 3,4. Therefore, the identification was continued by nested PCR of 16S rRNA, which has been shown to be highly sensitive,5,6 being able to detect as few as two organisms present in the reaction.6 However, we fully welcome the suggestion of Dance et al that further additional testing, eg, multilocus sequence typing, nucleotide sequence analysis, or PCR for the TTS1 gene, is needed to verify the identification of B. pseudomallei . We have previously asked a member of the International Melioidosis Society Committee to review our identification method; however, that request was declined at the time.…”
Section: Dear Editormentioning
confidence: 96%
“…As reported by Inglis et al, the API 20NE method identified only 37% of the B. pseudomallei isolates.2 B. pseudomallei has a high degree of phenotypic plasticity and the colony morphology varies greatly within and between samples 3,4. Therefore, the identification was continued by nested PCR of 16S rRNA, which has been shown to be highly sensitive,5,6 being able to detect as few as two organisms present in the reaction.6 However, we fully welcome the suggestion of Dance et al that further additional testing, eg, multilocus sequence typing, nucleotide sequence analysis, or PCR for the TTS1 gene, is needed to verify the identification of B. pseudomallei . We have previously asked a member of the International Melioidosis Society Committee to review our identification method; however, that request was declined at the time.…”
Section: Dear Editormentioning
confidence: 96%
“…The antimicrobial susceptibility pattern of clinical isolates showed 100% sensitivity to ceftazidime, imipenem, piperacillin–tazobactam, amoxicillin–clavulanic acid, and tetracycline by both disk diffusion and MIC methods in Bangladesh [ 47 ]. Intravenous antibiotics (ceftazidime and meropenem/imipenem) for the acute phase and oral antibiotics for the eradication phase are available in the local market (district and divisional level).…”
Section: Current Recommendations and Availability Of Measures Agaimentioning
confidence: 99%
“…Burkholderia pseudomallei is a Gram-negative bacterium that causes melioidosis, 1, 2 a 46 neglected tropical disease with an estimated 165,000 cases and 89,000 deaths per year. 1…”
Section: Introduction 45mentioning
confidence: 99%
“…6,19,20 The 70 prolonged nature of the melioidosis treatment schedule can lead to acquired resistance, a 71 significant event that has been linked to treatment failure and mortality in melioidosis patients 72 from the Northern Territory. 5 Prolonged and costly treatments are especially undesirable in 73 many regions where melioidosis is endemic, 1,2,8 and to overcome both intrinsic and acquired 74 antibiotic resistance, more efficacious therapeutics for the treatment of melioidosis are 75 required. 1…”
mentioning
confidence: 99%
See 1 more Smart Citation